STATUS OF SCHOOL TEACHER OF THE RENAISSANCE: THE PHENOMENON OF ST. PAUL’S SCHOOL - L. V. Sofronova; A. V. Khazina (Вестник Мининского университета, 2017)
The authors analyze the historical account that was little-known to the national historical and pedagogical tradition, namely «The Statute of St. Paul’s grammar school» established at St. Paul Cathedral on the initiative and at the expense of the cathedral’s dean John Colet (1467-1519), the famous English Christian thinker of the pre-Reformation time. The article observes that, despite the long-standing precedents, Colet’s foundation of a new school was perceived by contemporaries as an extraordinary event which was mentioned in the chronicles. The St. Paul’s School, free from ecclesiastical jurisdiction, was ruled by a secular body - the School Board of the Mercer-merchants («Mercers Wardens and Surveyors»). According to the Statutes, the material and social status of teachers at the school was in many ways much higher compared to the traditionally low status of teachers in the late medieval society. The high level of salaries, pensions for old age and disability, as well as the provision of free housing in a specially constructed teacher's building testify to Colet's high appreciation of the importance of the teachers’ role for the Christian education, spiritual and moral renewal of society. The authors put forward the first Russian translation of «The Statute of St. Paul’s grammar school»’ fragment concerning the teacher’s status and relative topics.